Flavivirus prM interacts with MDA5 and MAVS to inhibit RLR antiviral signaling - Liyan Sui; Yinghua Zhao; Wenfang Wang; Hongmiao Chi; Tian Tian; Ping Wu; Jinlong Zhang; Yicheng Zhao; Zheng-Kai Wei; Zhijun Hou; Guoqiang Zhou; Guoqing Wang; et al. (Cell & Bioscience, 2023)
Abstract Background Vector-borne flaviviruses, including tick-borne encephalitis virus (TBEV), Zika virus (ZIKV), West Nile virus (WNV), yellow fever virus (YFV), dengue virus (DENV), and Japanese encephalitis virus (JEV), pose a growing threat to public health worldwide, and have evolved complex mechanisms to overcome host antiviral innate immunity. However, the underlying mechanisms of flavivirus structural proteins to evade host immune response remain elusive. Results We showed that TBEV structural protein, pre-membrane (prM) protein, could inhibit type I interferon (IFN-I) production. Mechanically, TBEV prM interacted with both MDA5 and MAVS and interfered with the formation of MDA5-MAVS complex, thereby impeding the nuclear translocation and dimerization of IRF3 to inhibit RLR antiviral signaling. ZIKV and WNV prM was also demonstrated to interact with both MDA5 and MAVS, while dengue virus serotype 2 (DENV2) and YFV prM associated only with MDA5 or MAVS to suppress IFN-I production. In contrast, JEV prM could not suppress IFN-I production. Overexpression of TBEV and ZIKV prM significantly promoted the replication of TBEV and Sendai virus. Conclusion Our findings reveal the immune evasion mechanisms of flavivirus prM, which may contribute to understanding flavivirus pathogenicity, therapeutic intervention and vaccine development.